Electric vehicle regional management system based on the BSP model and multi-information fusion. (1st April 2021) - Zeng, Zhihui; Sun, Xintong
Abstract : Aiming at the problem of most electric vehicles (EV) sounding false alarms due to touches, an EV alarm regionalization management control system based on multi-information fusion and the BSP model is designed in the present study. The proposed system uses multiple sensors to detect the state of the EV, and realizes multi-sensor information fusion by the Lagrange interpolation method. The ZigBee networking technology is used to carry out the regional management of EV alarms, establish a BSP model, realize the synchronous transmission of system status detection signals, and finally complete the alarm function. The experimental results show that the false alarm rate of traditional EV alarm systems is about 85.5%, that of alarm systems that perform state monitoring without information fusion is about 11.3%, and that of the proposed alarm system that performs multi-information fusion simultaneously is greatly reduced to about 0.5%.